Social and Emotional Learning in Preschool Settings: A Systematic Map of Systematic Reviews - Djamnezhad, Dariush; Koltcheva, Nadia; Dizdarevic, Alma; Mujezinovic, Amila; Peixoto, Carla; Coelho, Vera; Achten, Mart; Kolumbán, Erika; Machado, Francisco; Hofvander, Björn (Frontiers in Education, 2021)
The preschool years presents an important opportunity to support children’s social and emotional development. Social and emotional learning (SEL) programs in early childhood education and care (ECEC) have gained an increased interest due to its potential to improve child health and educational outcomes. We aimed to identify existing systematic reviews on universal, curriculum-based SEL interventions in ECEC settings (children aged 0 to 7 years), assess their risk of bias, synthesize the findings and identify knowledge gaps. We undertook a systematic literature search in seven different databases. Reviews of studies without control groups were excluded. Each abstract and full text article was assessed independently, and disagreements were solved in consensus. Relevant reviews were assessed for bias using the ROBIS tool. Of 4912 records identified through database searches, two systematic reviews met the inclusion criteria. Both reviews were assessed as having a high risk of bias. The results were used to summarize existing knowledge and knowledge gaps. In conclusion, SEL interventions in preschool settings must be considered knowledge gaps. There is a need for more high-quality primary studies and further systematic reviews that adhere to strict scientific methods and address the overwhelming heterogeneity in field, in terms of interventions, settings and outcomes.